2015
DOI: 10.1111/bjet.12313
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between video lecture usage patterns and students' attitudes

Abstract: Videos have enhanced the value of teaching and learning, particularly in tertiary education. Recent studies have investigated students' attitudes toward video lectures for educational purposes; however, the relationship between students' attitudes and different usage patterns such as platforms used, video duration, watching period and students' experience, is yet to be explored. To investigate potential attitudinal differences among the diverse video lectures usage patterns, the present study incorporates resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 33 publications
(38 reference statements)
5
40
0
12
Order By: Relevance
“…Despite the great attention scholars and teaching practitioners have paid to understanding the effects of VL in higher education, there is still a paucity of information about the impact that VL have on online students' learning perceptions and experiences (Hsin & Cigas, ). Some studies focused on the usage of VL in specific online learning platforms, such as Khan Academy, Coursera and other MOOCs, while other scholars have investigated the usage patterns (Giannakos, Jaccheri, & Krogstie, ) or use of VL connected to academic assessment (Bouwmeester et al ., ; Gikandi, Morrow, & Davis, ). Hence, this study is to contribute to broadening our understanding of the relationship between students' perceptions of using VL in online classes and their learning experiences as well as the use of VL in online education.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great attention scholars and teaching practitioners have paid to understanding the effects of VL in higher education, there is still a paucity of information about the impact that VL have on online students' learning perceptions and experiences (Hsin & Cigas, ). Some studies focused on the usage of VL in specific online learning platforms, such as Khan Academy, Coursera and other MOOCs, while other scholars have investigated the usage patterns (Giannakos, Jaccheri, & Krogstie, ) or use of VL connected to academic assessment (Bouwmeester et al ., ; Gikandi, Morrow, & Davis, ). Hence, this study is to contribute to broadening our understanding of the relationship between students' perceptions of using VL in online classes and their learning experiences as well as the use of VL in online education.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, instructional videos are widely used in both campus-based and online courses [8][9][10][11][12][13]. The use of such videos in combination with face-to-face class instruction may be especially beneficial; several meta-analyses have found that hybrid or blended courses, which include both face-to-face and online instruction, are more effective than either traditional in-person courses or fully online courses [14,15].…”
Section: Benefits Of Online Supplementary Instructionmentioning
confidence: 99%
“…Ayrıca hem görsel öğelerin hem de sözel öğelerin kullanılması farklı öğrenme biçiminde öğrenebilen öğrenenlere kolaylık sağlamaktadır (Vural, 2013). Bu çeşitliliği sağlayan videolar, öğrenenlerin öğrenme süreçlerine karşı olan tutumlarını olumlu anlamda geliştirmektedir (Giannakos, Jaccheri & Krogstie, 2015 (2015) tarafından öğrenme ortamlarına yavaş yavaş girmekte olan güçlü teknolojiler olarak tanımlanmaktadır. Bu bağlamda, öğrenme ortamlarında çeşitli türlerde kullanılabilen ve içerisine etkileşimli yapıda olmasını sağlayan fonksiyonların gömülebildiği videoların, öğrenme ortamlarında kullanılmaya başlanması, öğrenme süreçlerinden alınacak verimin artması anlamında önemli bir gelişme olarak görülebilir.…”
Section: Türkçe Sürüm Girişunclassified
“…Using both visual and verbal elements facilitate learning for learners with different learning styles (Vural, 2013). Because of this feature, videos enhance the attitudes of students and value of teaching and learning (Giannakos, Jaccheri & Krogstie, 2015). Furthermore, the rapid development of video technology has been gaining an increasing attention.…”
Section: Introductionmentioning
confidence: 99%